Tocilizumab in COVID-19: The Cerrahpaşa-PREDICT score. Issue 9 (September 2021) - Eşkazan, Ahmet Emre; Balkan, İlker İnanç and Demirbaş, Kaan Can and Ar, Muhlis Cem and Karaali, Rıdvan and Sekibağ, Yonca and Mulamahmutoğlu, Sait and Yartaş Dumanlı, Güleren and Çakmak, Fatih and Özgür Yurttaş, Nurgül and Kurt, Furkan and Aladağ Kurt, Seda and Kuşkucu, Mert and Ürkmez, Seval and Börekçi, Şermin and Saribal, Devrim and Mete, Bilgül and Bavunoğlu, Işıl and Dikmen, Yalım and Aygün, Gökhan and Midilli, Kenan and Tabak, Fehmi
Abstract: Background: Cytokine release syndrome (CRS), characterized by overproduction of proinflammatory cytokines in the course of severe coronavirus disease 2019 (COVID-19), has been suggested as the major cause of mortality. Tocilizumab, a recombinant humanized monoclonal antibody against human IL-6 receptor, poses a therapeutic option for the treatment of CRS leading to severe acute respiratory syndrome in coronavirus-2 (SARS-CoV-2) infection. Methods: We performed a single-center retrospective study to reveal the outcome of COVID-19 patients on tocilizumab and proposed "the Cerrahpaşa-PREDICT score", a new clinical scoring system using clinical and laboratory parameters that would help predicting the 28-day mortality of COVID-19 patients receiving tocilizumab. Results: Eighty-seven patients (median age: 59 years) were included of whom 75.8% were male. Tocilizumab use significantly improved clinical and laboratory parameters. The 28-day mortality rate on tocilizumab was 16.1%. The Cerrahpaşa-PREDICT score, consisting of platelet counts, procalcitonin, D-dimer levels, SO2 R and the time from symptom onset to tocilizumab administration had a positive predictive value of 94.5% and negative predictive value of 92.9% for anticipating 28-day mortality. Conclusions: Severe COVID-19 should closely be monitored for the signs of hyperinflammation. We showed that administration of tocilizumab early in the course of the disease (prior to ICU admission) resulted in a favorable outcome. Close monitoring usually aids identifying patients who would benefit from tocilizumab. In this regard, the Cerrahpaşa-PREDICT score might serve as a practical tool for estimating the 28-day mortality in COVID-19 patients who received tocilizumab and would facilitate timely recognition of fatal cases to be evaluated for other therapeutic options.